2008
DOI: 10.1097/brs.0b013e31817e30fb
|View full text |Cite
|
Sign up to set email alerts
|

Use of Carboxymethylcellulose/Polyethylene Oxide Gel in Microdiscectomy With Interlaminectomy

Abstract: CMC/PEO gel after microdiscectomy with interlaminectomy appears safe to use and in a 3-year follow-up significantly reduces disability and leg pain scores compared with our conventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The difference in favor of Oxiplex ranged from 15% to 26% and duration of this benefit persisted for at least 6 months. 12,13 The results of this investigation demonstrated that Oxiplex had a statistically significant and clinically meaningful effect on the degree of reduction in leg pain from baseline, which confirms the findings from the studies performed in the United States 13 and Italy. 12 These observations support the role of Oxiplex in reducing leg pain among challenging patients with concomitant severe baseline back pain.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The difference in favor of Oxiplex ranged from 15% to 26% and duration of this benefit persisted for at least 6 months. 12,13 The results of this investigation demonstrated that Oxiplex had a statistically significant and clinically meaningful effect on the degree of reduction in leg pain from baseline, which confirms the findings from the studies performed in the United States 13 and Italy. 12 These observations support the role of Oxiplex in reducing leg pain among challenging patients with concomitant severe baseline back pain.…”
Section: Discussionsupporting
confidence: 81%
“…This significant reduction in leg pain (P = 0.0240) confirmed previous reports of significant reduction in leg pain from similar surgical procedures performed in Italy (26%, P = 0.0008, Assietti et al12 ) and the United States (P = 0.0123, Rhyne et al13 ).…”
supporting
confidence: 88%
See 3 more Smart Citations